2021
DOI: 10.1590/1982-7849rac2021200031.en
|View full text |Cite
|
Sign up to set email alerts
|

A Surge toward a Sustainable Future: Organizational Change and Transformational Vision by an Oil and Gas Company

Abstract: Context: reflecting the call being made by the United Nations to solve our current climate challenges and reduce companies’ CO2 emissions, there is a strong need for large corporations to not only employ the terminology of sustainable transitions, but to implement strategies and select new alternative sustainable solutions. Objective: this study fills a gap in the literature by developing and validating a model that helps researchers understand the factors that enable a large corporation undergoing a sustai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 86 publications
(86 reference statements)
0
2
0
1
Order By: Relevance
“…There were some minor changes in the factors' sentences, according to expert opinions, which were considered in the final version. Experts have been used to review and refine different factors in other studies as well, as indicated in (Ghaithan et al , 2021; Jaber, 2021; Kamble and Gunasekaran, 2021; Ronaghi and Mosakhani, 2022). This process ensured the content validity of the measurement instrument and confirmed its ability to measure what it was intended to measure.…”
Section: Methodsmentioning
confidence: 99%
“…There were some minor changes in the factors' sentences, according to expert opinions, which were considered in the final version. Experts have been used to review and refine different factors in other studies as well, as indicated in (Ghaithan et al , 2021; Jaber, 2021; Kamble and Gunasekaran, 2021; Ronaghi and Mosakhani, 2022). This process ensured the content validity of the measurement instrument and confirmed its ability to measure what it was intended to measure.…”
Section: Methodsmentioning
confidence: 99%
“…The paper "A surge toward a sustainable future: Organizational change and transformational vision by an oil and gas company" (Jaber, 2021) investigates drivers toward sustainability, specifically how institutional drivers of a large established corporation undergoing a sustainable transition influence certain action. This article employs quantitative data and takes a step forward toward examining the employees' role in selecting innovative sustainable projects such as renewable energy.…”
Section: The Special Issue the Special Issuementioning
confidence: 99%
“…A incorporação de práticas sustentáveis tem crescido no ambiente empresarial desde a formulação do conceito de sustentabilidade corporativa, tendo como base o Triple Bottom Line definido por Elkington (1994), independente do porte das empresas, desde pequenas a grandes corporações. A sustentabilidade pode ser vista como um compromisso que busca permitir a uma empresa desenvolver novas alternativas que sejam sustentáveis, visando assim alcançar novas perspectivas, tais como o desenvolvimento socioambiental, ao invés de focar somente em ganhos econômicos (Jaber, 2020).…”
Section: Introductionunclassified